STIMULASI KEMAMPUAN KLASIFIKASI PRA-MATEMATIKA (WARNA DAN BENTUK GEOMETRI) PADA ANAK USIA 4-5 TAHUN MELALUI PERMAINAN SORTING COLOR DI TK KHADIJAH 150 - Mutamimah, Siti; Wahyuningsih, Riris; Bahari, Jon Iskandar (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
Pre-mathematical classification is one aspect of cognitive development. Classification is important to introduce to train children to think logically from an early age and hone children's thinking power in managing information, namely observing the similarities and differences of objects so that they can add new knowledge for children. The purpose of this study was to stimulate children's pre-mathematical classification skills through color sorting games. Based on observations made at Khadijah Kindergarten 150, it was found that children's pre-mathematical classification abilities were still low because of the assumption that the compulsory learning in schools was reading, writing, and arithmetic. So that in learning activities the teacher only uses thematic books as the main learning resource, while the color sorting game is only used as a safety activity and is rarely applied. In this study using descriptive qualitative research from the data generated through observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman model. As for the validity of the data using Source Triangulation. The subjects in this study were principals and teachers of class A2, and children aged 4-5 years in group A2 at Khadijah 150 Kindergarten. Based on the results of research and data analysis carried out collaboratively between teachers and researchers resulted in the conclusion that the color sorting game can stimulate pre-mathematical classification skills (geometric shapes and colors) in children aged 4-5 years at Khadijah Kindergarten 150 in the 2021/2022 academic year optimally .